2021
DOI: 10.1093/molbev/msab369
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection and Enhancer Evolution Shaped Lifespan and Body Mass in Great Apes

Abstract: Within primates, the great apes are outliers both in terms of body size and lifespan, since they include the largest and longest-lived species in the order. Yet, the molecular bases underlying such features are poorly understood. Here, we leveraged an integrated approach to investigate multiple sources of molecular variation across primates, focusing on over ten thousand genes, including ∼1,500 previously associated with lifespan, and additional ∼9,000 for which an association with longevity has never been sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 168 publications
(210 reference statements)
0
11
0
Order By: Relevance
“…Tejada-Martinez et al [40] also focused on protein evolution in their study of lifespan and body mass in primates, although they then linked their findings to enhancer evolution. Their approach was to perform phylogenetic regressions, relating dN/dS to maximum lifespan and body mass for around 10,000 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tejada-Martinez et al [40] also focused on protein evolution in their study of lifespan and body mass in primates, although they then linked their findings to enhancer evolution. Their approach was to perform phylogenetic regressions, relating dN/dS to maximum lifespan and body mass for around 10,000 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Their approach was to perform phylogenetic regressions, relating dN/dS to maximum lifespan and body mass for around 10,000 genes. In contrast to Kowalczyk et al [15], Tejada-Martinez et al [40] focus on positive (directional) selection on protein-coding genes rather than conservation. The authors identified 276 candidate genes whose rate of adaptive evolution positively correlated with maximum life span in a phylogenetic context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other mammalian lineages, the maximum life span and body mass are correlated in primates, and the great apes are the largest body size and long-lived species among them. Tejada-Martinez et al (2022 ) investigated the molecular evolution in coding genes and cis-regulatory sequences and gene expression evolution related to the development and maintenance of maximum lifespan and body size in the great apes and their association with pathways related to cancer suppression. They found only five genes with positive selection signals for the great ape lineage (IRF3, SCRN3, DIAPH2, GASK1B, and SELENO), all of which have functions related to cancer development and inflammatory responses.…”
Section: Mechanisms To Evade Cancermentioning
confidence: 99%
“…The authors also identified footprints of evolution related to SINE-Vntr-Alu (SVA) insertions and LTR transposons, reinforcing the importance of the action of these transposable elements in the evolution of great apes' gene-regulatory networks, especially in humans ( Trizzino et al , 2017 ). The results of Tejada-Martinez et al (2022 ) show that the evolution of strategies for cancer resistance in the primate lineage is quite diverse, with modifications that can be found at the coding, expression, and regulatory levels, and that although the great apes lineage provides evidence of specific changes capable of giving greater longevity to the species of the group, the understanding of the relationship with cancer resistance is still developing for nonhuman species and needs to be further investigated.…”
Section: Mechanisms To Evade Cancermentioning
confidence: 99%